2016
DOI: 10.1021/acsmedchemlett.6b00234
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent Liver X Receptor β Agonists

Abstract: Introducing a uniquely substituted phenyl sulfone into a series of biphenyl imidazole liver X receptor (LXR) agonists afforded a dramatic potency improvement for induction of ATP binding cassette transporters, ABCA1 and ABCG1, in human whole blood. The agonist series demonstrated robust LXRβ activity (>70%) with low partial LXRα agonist activity (<25%) in cell assays, providing a window between desired blood cell ABCG1 gene induction in cynomolgus monkeys and modest elevation of plasma triglycerides for agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…Reaching isoform selectivity by rational structure-based drug design has proven to be difficult since the ligand-binding pockets (LBPs) of LXRα and LXRβ are virtually identical 3133 . Nevertheless, some degree of selectivity in binding and functional assays was achieved for a number of compounds 3336 , including two ligands displaying reduced lipogenic effects and reaching clinical evaluation: WAY-252623 (LXR-623) 3739 and BMS-852927 40,41 . However, even optimized compounds retain substantial affinity for LXRα, and therefore it is questionable whether their reduced hepatic activities could be explained solely by modestly improved LXRβ selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Reaching isoform selectivity by rational structure-based drug design has proven to be difficult since the ligand-binding pockets (LBPs) of LXRα and LXRβ are virtually identical 3133 . Nevertheless, some degree of selectivity in binding and functional assays was achieved for a number of compounds 3336 , including two ligands displaying reduced lipogenic effects and reaching clinical evaluation: WAY-252623 (LXR-623) 3739 and BMS-852927 40,41 . However, even optimized compounds retain substantial affinity for LXRα, and therefore it is questionable whether their reduced hepatic activities could be explained solely by modestly improved LXRβ selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since these discoveries, the design of LXR␤-specific synthetic agonists to treat metabolic disorders or inflammatory diseases, avoiding de novo lipogenesis, has been a challenging effort (7). Interestingly, recent studies have shown promising therapeutic potential of novel compounds (23,24) with immunomodulatory and antineoplasic activities (25).…”
mentioning
confidence: 99%
“…Identifying LXRβ‐selective ligands has proven to be challenging due to the high level of protein sequence homology between the ligand‐binding pockets of the two subtypes. While small molecules with LXRβ selectivity in vitro have been described we have tested several of these compounds in vivo and have been unable to identify a small molecule LXR ligand that does not regulate LXR target genes in LXRβ knockout mice (i.e., can activate LXRα. I. Schulman, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of subtype‐selective LXR ligands has proven to be difficult due to the high amino acid identity in the ligand‐binding pocket of the two receptors (only one amino acid differs between the two). Nevertheless, several small molecules with selectively for LXRβ in biochemical and cell‐based assays have been described although the specificity necessary to limit hyperlipidemia upon multiple dosing in humans has not been achieved .…”
Section: Lxrs and Metabolic Diseasementioning
confidence: 99%